Parents' Parenting Pattern Description Ofslow Learner Children In Pandemic Situation Coronavirus Disease 19 - Dea Adhe Rizky; Nadhirotul Laily; Muhimmatul Hasana (Universitas Negeri Padang, 2022)
This study examines